2008
DOI: 10.1159/000160212
|View full text |Cite
|
Sign up to set email alerts
|

The Role of High-Sensitivity C-Reactive Protein in Asymptomatic Intra- and Extracranial Large Artery Diseases

Abstract: Background: It remains unclear whether high-sensitivity CRP (hs-CRP) is predictive of atherosclerosis in the intracranial artery. The aim of this study is to assess the role of hs-CRP in asymptomatic intracranial artery occlusive diseases. Methods: Of the 3,366 apparently healthy subjects who received a brain checkup, 138 with ≧25% intracranial artery stenosis on magnetic resonance angiography, 267 with ≧25% extracranial carotid artery stenosis on B-mode ultrasonography and 435 without intracranial artery or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 61 publications
0
10
1
1
Order By: Relevance
“…We found that CRP levels were significantly higher in subjects with ECAD than in those with ICAD, similar to previously reported. 15,19 Resistin is a protein secreted by adipocytes and related to insulin resistance in rodents, whereas in humans it is mainly secreted by inflammatory cells and has been reported as a marker of coronary and carotid atherosclerosis. 21,22 In the present study, resistin was independently associated with atherosclerotic burden, especially with combined ECAD and ICAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that CRP levels were significantly higher in subjects with ECAD than in those with ICAD, similar to previously reported. 15,19 Resistin is a protein secreted by adipocytes and related to insulin resistance in rodents, whereas in humans it is mainly secreted by inflammatory cells and has been reported as a marker of coronary and carotid atherosclerosis. 21,22 In the present study, resistin was independently associated with atherosclerotic burden, especially with combined ECAD and ICAD.…”
Section: Discussionmentioning
confidence: 99%
“…Few retrospective studies have evaluated inflammatory and metabolic markers associated with the different location (extra-versus intracranial) of cerebral atherosclerosis, [15][16][17][18] with only one study performed in asymptomatic subjects. 19 A proinflammatory state and an impaired fibrinolysis have also been associated with progression of symptomatic intracranial atherosclerosis. 20 Prospective studies on biomarkers associated with asymptomatic intracranial atherosclerosis are lacking.…”
mentioning
confidence: 99%
“…In support of this mechanism, several inflammatory biomarkers, and particularly high sensitivity C-reactive protein, have been identified as predictors of the risk of recurrent stroke in individuals with intracranial atherosclerosis [5]. The role of these markers is, however, less clear in predicting a first stroke in individuals with asymptomatic intracranial atherosclerotic stenosis [53]. …”
Section: Pathophysiology Of Intracranial Atherosclerosismentioning
confidence: 99%
“…Degradation of extracellular matrix components particularly by matrix metalloproteinases (MMPs), together with an increased inflammatory reaction is the main reason for plaque progression to rupture and consequent neurological symptoms [3,5,6]. Thus, MMPs and inflammatory factors may also serve as possible markers of plaque instability [7,8,9,10,11,12]. Several studies have already demonstrated increased levels of some MMPs and inflammatory proteins in the blood of patients with advanced carotid atherosclerosis [13,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%